Making room for everyone: Assessing housing needs and suitability in Waterloo Region, Ontario via time, space, and equity lenses - Petric, Alex; Parker, Dawn C.; Geobey, Sean; Wright, Kirsten (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2024)
Over the past decade, the Region of Waterloo experienced significant population growth and housing construction, but housing costs have continued to rise. To tackle the broader housing crisis affecting Ontario and Canada, calls for increased housing construction have grown, but advocates often emphasize quantities of homes needed without considering housing type, household composition, or equity considerations. We analyze public data for Census Tracts and across the Region of Waterloo to compare housing construction and population growth and to assess housing indicators across socio-demographic indicators to highlight groups deserving greater attention in housing needs assessments. We observe 1) a need for both greater housing supply and greater housing diversity, 2) socio-demographic inequality in housing suitability outcomes, and 3) a need to include equity-based analysis in housing and land needs assessments. We therefore propose municipal policy options to support improved housing supply, diversity, and analysis, including a greater focus on developing “missing middle” housing.